2007
DOI: 10.1002/bit.21713
|View full text |Cite
|
Sign up to set email alerts
|

Microparticle‐enhanced cultivation of filamentous microorganisms: Increased chloroperoxidase formation by Caldariomyces fumago as an example

Abstract: Microparticle-enhanced cultivation (MPEC) was applied as a novel method for improved biomass and product formation during cultivation of filamentous microorganisms. Exemplarily, chloroperoxidase (CPO) formation by Caldariomyces fumago was analyzed in the presence and absence of microparticles of different size. Particles of $500 mm in diameter had no effect on growth morphology or productivity of CPO formation by C. fumago. In contrast particles of 42 mm in diameter led to the dispersion of the C. fumago mycel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(143 citation statements)
references
References 28 publications
7
134
1
1
Order By: Relevance
“…So far this only allowed a partial control of morphology by the initial pH-value, the impeller speed or the initial spore concentration. 2 In a pioneering study, the addition of micro particles to the culture was recently shown to alter fungal morphology 3 which was recently utilized to precisely adjust different distinct morphological forms in A. niger. 4 The strong impact of microparticles on A. niger is exemplified for the addition of talc or aluminium oxide to the culture medium prior to inoculation (Fig.…”
Section: Targeted Morphology Engineering For Improved Enzyme Productionmentioning
confidence: 99%
“…So far this only allowed a partial control of morphology by the initial pH-value, the impeller speed or the initial spore concentration. 2 In a pioneering study, the addition of micro particles to the culture was recently shown to alter fungal morphology 3 which was recently utilized to precisely adjust different distinct morphological forms in A. niger. 4 The strong impact of microparticles on A. niger is exemplified for the addition of talc or aluminium oxide to the culture medium prior to inoculation (Fig.…”
Section: Targeted Morphology Engineering For Improved Enzyme Productionmentioning
confidence: 99%
“…Various process parameters and ingredients are known to influence fungal morphology 1 . Since optimal productivity correlates strongly with a specific morphological form, the fungal morphology often represents the bottleneck of productivity in industrial production.A straight forward and elegant approach to precisely control morphological shape is the addition of inorganic insoluble micro particles (like hydrous magnesium silicate, aluminum oxide or titanium silicate oxide) to the culture medium contributing to increased enzyme production [2][3][4][5][6] . Since there is an obvious correlation between micro particle dependent morphology and enzyme production it is desirable to mathematically link productivity and morphological appearance.…”
mentioning
confidence: 99%
“…Bacterial production is attractive as a commercial manufacturing process, compared with fungal production, since production by filamentous fungi sometimes encounters technical problems, such as low productivity due to insufficient control of growth and morphology and difficult handling for filtration and extraction due to high viscosity (43)(44)(45)(46)(47). The gene cluster for nectrisine biosynthesis could provide a foundation to develop a microbial production system for nectrisine and its intermediates, such as 4-amino-4-deoxyarabinitol, through genetic engineering.…”
Section: Discussionmentioning
confidence: 99%